International Development of the Alzheimer's Patient Partners Life Impact Questionnaire (APPLIQue). (27th August 2020) - McKenna, Stephen P.; Rouse, Matthew; Heaney, Alice; Hagell, Peter
Aim: Informal caregivers play a vital role in the care of people with Alzheimer's Disease (AD), yet caregiving is associated with caregivers' burden. The initial objective of the study was to develop a new outcome measure to assess quality of life (QoL) in AD caregivers. Methods: Informal (non-professional) caregivers providing 75% or more of the care activities for, and living in the same household as, a person with AD were invited to take part in the study. Qualitative interviews (N = 40) were conducted with AD caregivers in the UK and thematic analyses were applied to generate a pool of potential items. A draft questionnaire was produced and adapted for use in Italy, Spain, Germany and the US. In each of the 5 countries, cognitive debriefing interviews (N = 76) were conducted to determine the questionnaire's face and content validity, followed by a postal validation survey (N = 268). The data from these surveys were combined to reduce the number of items and assess the new questionnaire's psychometric properties. Results: Thematic analysis of the UK interview transcripts generated a draft questionnaire, which was successfully translated into each additional language. The items were well accepted and easy to complete. However, reanalysis of the qualitative interview data revealed that spousal and non-spousal caregivers identified different experiences of caregiving. A review of the item pool indicated that items were primarily targeted at spousal caregivers. Therefore, further analyses of the postal survey data included spousal caregivers only (n = 116). The results supported scaling assumptions (e.g., corrected item-total correlations ≥0.32), targeting (e.g., floor/ceiling effects <2.5%), internal consistency (α ≥0.93) and test-retest reliability (rs = 0.88) of the new questionnaire, according to classical test theory. Assessment of external construct validity yielded results in accordance with a priori expectations. QoL scores were most strongly related to scores on the emotional reactions sections of the Nottingham Health Profile and the General Well-Being Index. The new questionnaire was found to be capable of detecting meaningful differences between respondents; spousal caregivers had worse QoL when the person with AD was confused (p < .001), could not be left alone (p < .001), did not recognize the caregiver (p < .001), was incontinent (p < .05), and wandered around the house (p = .01). Conclusions: The Alzheimer's Disease Patient Partners Life Impact Questionnaire (APPLIQue) is a questionnaire specific to spousal caregivers of people with AD. Data support its scaling assumptions and it exhibits excellent psychometric properties according to classical test theory. The questionnaire is recommended for use in intervention studies where the QoL of spousal caregivers is of interest.